Desain Interaksi Aplikasi Pengendali Smart Home Menggunakan Smartphone Android - Tri Oktavia Mayasari; Edita Rosana Widasari; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Smart home were developed to do some daily activity automatically. To operate or monitor some devices in home wirelessly using smartphone. Nowadays, there's lot of smarthome control application based on smartphone that being developed but without paying attention to the basic principle of design, that's why in this research we will make smart home control application using android smartphone with bluetooth connectivity that could control some devices with basic design principle of human and computer interaction in mind with user friendly feature. Those priciple were designed to increase usability of the application to ease the user in operating smart home. Design process used in this application development is begin with what method that we wanted, and the we analyze the skenario and HTA the implement the interaction design principle. Usability test of the application were done using verification and observation.The result of verification test were work as predicted skenario. While in observation test, user need 43,1 second in average. Analysis of usability test by giving USE questionnaires to 30 respondents with the provision 15 users with basic knowledge of IT and 15 non IT with 5 categories based on the Likert scale ratings. usefulness, ease of use and easy to understand and satisfaction category get 4 (agree). From this research, we can conclude that this application is having high usability and from the observation test, user have agreed that this application would help them in controlling their home.